A makara and a simhamukha in half medalion of the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Decorative motifs on the external wall (proper right), details of decoration: a makara (crocodile) and a simhamukha (lion face) in half medalion (proper left) of the Sitaleshwar Temple.